Copper- and ligand-free sonogashira reaction catalyzed by Pd(0) nanoparticles at ambient conditions under ultrasound irradiation - Gholap, Atul R.; Venkatesan, K.; Pasricha, R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Organic Chemistry, 2005)
The Sonogashira reaction proceeds at ambient temperature (30 degrees C) in acetone or room-temperature ionic liquid, 1,3-di-n-butylimidazolium tetrafluoroborate ([bbim]BF4), as solvent under ultrasound irradiation to give enhanced reaction rates, excellent chemoselectivity, and high yields in the absence of a copper cocatalyst and a phosphine ligand. TEM analysis showed the formation of stable, crystalline, and polydispersed Pd(0) nanoparticles as catalyst for the reaction.

Novel one-pot synthesis of 2-Aryl-4(3H)-quinazolinones using room temperature ionic liquid as reaction medium as well as promoter - Potewar, T. M.; Nadaf, R. N.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Synthetic Communications, 2005)
An efficient one-pot synthesis of 2-aryl-4(3H)-quinazolinones from 2-amino benzamides and substituted benzoyl chlorides in a room temperature ionic liquid is described. Compared with the classical reaction conditions, this new synthetic method has the advantages of recyclability of ionic liquid, very good to excellent yields (78-92%), the absence of hazardous and expensive catalysts, and easy workup procedures giving rise to a process with minimum waste.
Keywords: 2-amino benzamide; 2-aryl-4(3H)-quinazolinones; benzoyl chlorides; Ionic liquid

Room temperature ionic liquid promoted improved and rapid synthesis of 2,4,5-triaryl imidazoles from aryl aldehydes and 1,2-diketones or alpha-hydroxyketone - Siddiqui, S. A.; Narkhede, U. C.; Palimkar, S. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Tetrahedron, 2005)
An improved and rapid one-pot synthesis of 2,4,5-triaryl imidazoles in a room temperature ionic liquid is described, which does not need any added catalyst. Different ionic liquids based on 1-n-butyl and 1,3-di-n-butyl imidazolium salts were screened and their efficacy in terms of acidity and polarity have been correlated with yields and reaction period. The one-pot methodology resulting in excellent isolated yields in short reaction times is characterized by simple work up procedures and efficient recovery and recycling of the ionic liquid, which acts as a promoter. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 2-Diketones; 4; 5-triaryl imidazoles; alpha-hydroxyketone; ammonium acetate; benzaldehydes; ionic liquid (IL)

Copper-, ligand- and solvent-free synthesis of ynones by coupling acid chlorides with terminal alkynes - Palimkar, Sanjay S.; Kumar, P. Harish; Jogdand, Nivrutti R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron Letters, 2006)
A general and efficient copper-, ligand- and solvent-free synthesis of ynones by coupling of a wide range of acid chlorides with terminal alkynes catalyzed by palladium(II) acetate at room temperature is reported. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ligandless; neat; ynones

Enantioselective synthesis of (+)-(S,S)-reboxetine - Siddiqui, Shafi A.; Narkhede, Umesh C.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Synlett, 2006)
An efficient enantioselective synthesis leading directly to (+)-(S,S)-reboxetine has been described from commercially available trans-cinnammyl bromide using Sharpless asymmetric dihydroxylation as the key step.
Keywords: coupling; Dihydroxylation; Hydrogenation; reboxetine; trans-cinnamyl bromide

Ionic liquid promoted facile one-pot synthesis of 1-pyridylimidazo[1,5-a]pyridines from dipyridylketone and aryl aldehydes - Siddiqui, Shafi A.; Potewar, Taterao M.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Synthesis-Stuttgart, 2006)
A highly efficient one-pot methodology has been developed to synthesize a class of substituted 1-pyridylimidazo[ 1,5-a]pyridines, using Bronsted acidic ionic liquid 1-butylimidazolium tetrafluoroborate, [Hbim]BF4 in excellent isolated yields in the absence of any catalyst. The methodology is characterized by simple work-up procedures along with efficient recovery and recycling of the ionic liquid, which acts as a reaction medium as well as a promoter.
Keywords: 5-a]pyridines; Aldehyde; ammonium acetate; heterocycles; imidazo[1; ionic liquids

Ligand-, copper-, and amine-free one-pot synthesis of 2-substituted indoles via Sonogashira coupling 5-endo-dig cyclization - Palimkar, Sanjay S.; Kumar, P. Harish; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron, 2006)
Results of the optimized conditions for the one-pot synthesis of 2-substituted indoles via palladium acetate catalyzed tandem Sonogashira coupling 5-endo-dig cyclization at room temperature under ultrasonic irradiation and standard stirred conditions are described. Electron-donating and electron-withdrawing groups present in both Coupling partners were well tolerated under these mild conditions. A copper-, ligand- and amine-free condition is an important feature of this protocol. Significant enhancement of reaction rates was observed for the reactions employing ultrasonic irradiation. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 5-endo-dig cyclization; Indole; synthesis; Ultrasound

Remarkably rapid regioselective synthesis of beta-enaminones using silica chloride in a heterogeneous as well as an ionic liquid in a homogeneous medium at room temperature - Gholap, Atul R.; Chakor, N. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Molecular Catalysis A-Chemical, 2006)
{Silica chloride as a heterogeneous catalyst has been used for the regioselective synthesis of P-amino-a,P unsaturated esters and ketones. Similar regioselective synthesis was also performed using an ionic liquid 1-n-butyl imidazolium tetrafluoroborate [
Keywords: direct oxidation of H-2 to H2O2; H2O2 decomposition; H2O2 hydrogenation; Promoting action of chloride or bromide anions; supported Pd catalysts

Novel one-pot three-component synthesis of 2,4-disubstituted-3H-benzo[b][1,4]diazepines in water - Palimkar, Sanjay S.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Green Chemistry, 2007)
A novel green and efficient one-pot three-component synthesis of 2,4-disubstituted-3H-benzo[b][1,4]diazepines in excellent isolated yields has been reported. The methodology initially involves the formation of ynones via coupling of a wide range of acid chlorides with terminal alkynes catalysed by Pd(OAc)(2) under copper-, ligand- and solvent-free conditions in just 10 min at rt followed by the Michael addition and cyclocondensation of o-phenylenediamines added in situ using water as a solvent at reflux temprature. In addition, the structure of the benzodiazepine was confirmed to be the diimino molecule and not the enamine by X-ray crystallographic analysis of the benzodiazepine 4b. The methodology is suitable for the operation in combi-chem mode to generate libraries of a diverse array of benzodiazepines. The methodology has been successful in achieving the twin green chemistry objectives of a solvent and ligand free operation and the use of water as a non-hazardous, inexpensive and readily available solvent in the sequential reaction steps performed in situ, thus combining the features of both economic and environmental advantages.

Efficient synthesis of 1,8-dioxo-octahydro-xanthene derivatives promoted by a room temperature ionic liquid at ambient conditions under ultrasound irradiation - Venkatesan, K.; Pujari, Suresh S.; Lahoti, Rajgopal J.; Srinivasan, K. V. (Ultrasonics Sonochemistry, 2008)
The condensation reaction involving an aldehyde and diketone was efficiently promoted by the Ionic liquid, [Hbim]BF(4) (IL) as a reaction medium with methanol as co-solvent at ambient temperature under ultrasonic irradiation to afford the corresponding 1,8-dioxo-octahydroxantliene (xanthene) derivatives in excellent yields. The advantages of this method include among others the use of a recyclable, non-volatile ionic liquid, which promotes this protocol under ambient temperature without the requirement of ally added catalyst. The reaction times and yields are compared with p-TSA catalyzed synthesis of xanthenes under thermal conditions, which is also reported for the first time under our reaction conditions. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: aldehydes; ambient conditions; Bronsted acidity; dimedone; Ionic liquid; Ultrasound; Xanthenes